Self-efficacy beliefs of adolescents - Pajares, Frank; Urdan, Timothy C. (Emerald Publishing Limited : IAP - Information Age Pub., Inc., 2006)
The introduction of the psychological construct of self-efficacy is widely acknowledged as one of the most important developments in the history of psychology. Today, it is simply not possible to explain phenomena such as human motivation, learning, self-regulation, and accomplishment without discussing the role played by self-efficacy beliefs. In this, the fifth volume of our series on adolescence and education, we focus on the self-efficacy beliefs of adolescents. We are proud and fortunate to be able to bring together the most prominent voices in the study of self-efficacy, including that of the Father of Social Cognitive Theory and of self-efficacy, Professor Albert Bandura. It is our hope, and our expectation, that this volume will become required reading for all students and scholars in the areas of adolescence and of motivation and, of course, for all who play a pivotal role in the education and care of youth.
Keywords: Self-efficacy.; Adolescent psychology.; Psychology -- Developmental -- Adolescent.; Child, developmental and lifespan psychology.; Age groups: adolescents.; elektronické knihy; electronic books